Membangun Sistem Informasi Pencatatan Penjualan Pada PT. Anugrah Langgeng Mukti Baturaja Menggunakan PHP dan MYSQL - Ulan; Salamudin; Haris (Jurnal Informatika dan Komputer (JIK), 2022)
The development of technology and information, especially in the advancement of computer technology, is very beneficial for humans because it is very helpful in completing various jobs. In this case, PT Anugrah Langgeng Mukti still uses a simple system and manual recording, resulting in difficulties in recording sales transactions between admin and marketing when making delivery notes as a result it takes quite a long time. For this reason, it is necessary to find easy steps in registering customers, registering material orders, and the process of making delivery notes. Computerized data collection is a very efficient step because data collection can be done quickly and accuracy can be guaranteed. In conducting the research, a laptop with a Windows 7 operating system was used with supporting applications for Xampp and Sublime Text 3. This system was developed using the PHP programming language and MySQL as the database. The data collection method used in this research is the observation method, the interview method, and the reference method. From the results of this study, an Information System for Recording Sales of PT Anugrah Langgeng Mukti was obtained which has several interconnected tables. This information system is used to input data, enter customer orders and produce output in the form of delivery notes of PT Anugrah Langgeng Mukti and reports related to customer data, materials, and cars.